Cuisinomics: MS-based untargeted approach reveals chemical modulation by a recipe during home cooking. (December 2020) - Rinaldi de Alvarenga, José Fernando; Quifer-Rada, Paola; Hurtado-Barroso, Sara; Illan, Montserrat; Torrado-Prat, Xavier; Lamuela-Raventós, Rosa M.
Graphical abstract: Highlights: Untargeted approach reveals the presence of new compounds to be explored on food. Onion and garlic increase phytoprostanes on tomato sauce. Cooking time increases hydroxycinnamic acid derivatives on cooked food. Cooking time increases 4-dihydroxyphenylglycone on cooked food. Polyphenol content could be modulated by ingredients and cooking time. Abstract: Most of daily eaten food are cooked, which helps in absorbing nutrients and phytochemicals, but at the same time it can decrease its content. Currently, the impact of cooking has been studied that could influence food health related compounds, but they have a limited view of compounds by not consider molecular structural modifications and new compounds formation. An untargeted approach using LC-ESI-LQT-Orbitrap-MS/MS and univariate/multivariate statistical analysis was applied to understand how the preparation of a recipe, varying its ingredients (olive oil, 5–10%; onion, 20–40%; and garlic, 2–4%) and cooking time, could modulate the chemical profile of a tomato sofrito sauce. The presence of unexplored compounds that may have a beneficial effect on health, such as phytoprostanes, hydroxycinnamic acid amides and compounds such as 3, 4 dihydroxyphenylglycone was revealed. Moreover, cooking was able to modulate the content of compounds like aminoacids, thiosulfates or phenolics and could be used as a tool to increase these molecules. The untargeted approach on cooking allows to use a recipe as a tool to improve a chemical profile of a dish, which opens the view for new dietary recommendations by cuisine to improve our diet, habits and health.